Identification of Tick-Borne Pathogens and Genotyping of Coxiella burnetii in Rhipicephalus microplus in Yunnan Province, China - Jiao, Jun; Zhang, Jianing; He, Peisheng; OuYang, Xuan; Yu, Yonghui; Wen, Bohai; Sun, Yi; Yuan, Qinghong; Xiong, Xiaolu (Frontiers in Microbiology, 2021)
Rhipicephalus microplus, a vector that can transmit many pathogens to humans and domestic animals, is widely distributed in Yunnan province, China. But few reports on the prevalence of tick-borne pathogens (TBPs) in Rh. microplus in Yunnan are available. The aim of this study was to detect TBPs in Rh. microplus in Yunnan and to analyze the phylogenetic characterization of TBPs detected in these ticks. The adult Rh. microplus (n = 516) feeding on cattle were collected. The pool DNA samples of these ticks were evaluated using metagenomic next-generation sequencing (mNGS) and then TBPs in individual ticks were identified using genus or group-specific nested polymerase chain reaction (PCR) combined with DNA sequencing assay. As a results, Candidatus Rickettsia jingxinensis (24.61%, 127/516), Anaplasma marginale (13.18%, 68/516), Coxiella burnetii (3.10%, 16/516) and Coxiella-like endosymbiont (CLE) (8.33%, 43/516) were detected. The dual co-infection with Ca. R. jingxinensis and A. marginale and the triple co-infection with Ca. R. jingxinensis, A. marginale, and CLE were most frequent and detected in 3.68% (19/516) and 3.10% (16/516) of these ticks, respectively. The results provide insight into diversity of TBPs and their co-infections in Rh. microplus in Yunnan province of China, reporting for the first time that C. burnetii had been found in Rh. microplus in China. Multilocus variable number tandem repeats analysis with 6 loci (MLVA-6) analysis discriminated the C. burnetii detected in Rh. microplus in Yunnan into MLVA genotype 1, which is closely related to previously described genotypes found primarily in tick and human samples from different regions of the globe, indicating a potential public health threat posed by C. burnetii in Rh. microplus in Yunnan.